Manejo de alimentación complementaria en los lactantes que asisten a cosulta externa en el Hospital Universitario de Motupe en el periodo diciembre 2015 - septiembre 2016. - Íñiguez León, Jonathan Leonardo (2017)
Complementary Feeding (CF) is defined as the process in which foods other than breast milk or formula are introduced into the diet of infants. The main objective of the next research was to determine the management of Complementary Feeding in infants from 6 to 23 months attending an External Consultation at the University Hospital of Motupe in Loja city. This study was carried out on mothers or caregivers of infants, it is qualitative, descriptive, cross-sectional type. The data were obtained through a survey. Within the results it was found that the infants had a normal nutritional status, the Complementary Feeding was started at 6 months of age, infants received foods containing gluten before the age of eight months, consumption of citrus fruits before the year of age, in most infants salt and sugar are added to their food and the amount of food is less than that recommended by the Ministry of Public Health guidelines. In conclusion, infants do not have adequate management of Complementary Feeding. Key words: Infants, Complementary Feeding, Management.